Analiza mowy ciała dziennikarzy sportowych na przykładzie Michała Pola oraz Mateusza Borka = Body language analysis of sports journalists using an example Michał Pol and Mateusz Borek - Michalczyk, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article is devoted to analyze the gestures of Michał Pol and Mateusz Borek, the most popular Polish sports journalists, in the selected video materials. My research focuses on nonverbal communication which reinforce the message but, on the other hand, it can also reveal the speaker`s hidden intentions. The purpose of this article is also to make the readers aware of the value of gestures and facial expression in the communication between the journalist and the recipient of the message.
Keywords: komunikacja; komunikaty międzyludzkie; mowa ciała; analiza przekazu; communication; interpersonal messages; body language; the analysis of the message